An Ayurvedic Approach of PCOS (International Journal of Ayurveda and Pharma Research, 2024)
The polycystic ovary syndrome (PCOS) is an endocrine, metabolic, reproductive and dermatological disturbance affecting women and is the foremost cause anovulatory infertility. The poorly understood etiopathogenesis contributes adversely to this burning health problem of women. Maximum cardinal features of PCOS like menstrual irregularities, obesity, hirsutism, infertility, polycystic ovaries are found in Vata-Kaphaja Artava Dushti/ Granthibhoot Aartav dusthi where in other systemic involvement may be justified based on the Dosha Lakshanas of Vata and Kapha. Though the disease PCOS is not mentioned directly in any of the classics of Ayurveda, it may be understood on the basis of Dosha Dushti, involvement of Dushya, Srotas, Ama, Agni, Adhistana and Vyadhi Lakshana. Granthibhuta Artava Dushti is characterized by Dushti Lakshana of both Vata and Kapha, scanty menstrual bleeding with or without association of pain and anovulation.